RITUAL KEMATIAN ETNIS TIONGHOA DI KOTA PEKANBARU - Anggara, Bima; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Funerals are usually a last tribute to the deceased. Everyone has a different belief and confidence, as ethnic Chinese who believe death by being cremated and buried. Cremation rituals of ethnic Chinese is very different from other ethnic death ritual cremation ritual itself is done varies according to religion and belief. The cremation ritual is not only done by the Buddhist religion alone but also the Confucian religion, Catholic, Christian also perform cremation in accordance with the request of the deceased and they are ethnic Chinese. not just ritual cremation are used in traditional Chinese funerals, but the ethnic Chinese also used the burial rituals as other religious death rituals. Of the above phenomena penlis interested examines interesting facts about the act of selecting the death ritual and the influence of socio-economic factors that lie behind them, lau researchers will study the rituals of death cremation and burial, the informant who studied amounted to 4 people, a population that is 2 of informants whose family members use death ritual cremation and 2 informant whose family members put on the death ritual burial. Data retrieval research conducted by interview, observation and documentation. Interviews were conducted is a structured interview where researchers first prepare interview guidelines. lau researchers will study the rituals of death cremation and burial, informants studied amounted to 4 people, a population that is 2 of informants whose family members use the death ritual cremation and 2 informant whose family members put on the death ritual burial. Data retrieval research conducted by interview, observation and documentation. Interviews were conducted is a structured interview where researchers first prepare interview guidelines. lau researchers will study the rituals of death cremation and burial, informants studied amounted to 4 people, a population that is 2 of informants whose family members use the death ritual cremation and 2 informant whose family members put on the death ritual burial. Data retrieval research conducted by interview, observation and documentation. Interviews were conducted is a structured interview where researchers first prepare interview guidelines.Keywords: Chinese, Cremation, Burials